F-SAL: A Framework for Fusion Based Semi-automated Labeling With Feedback - Zaidi, Ahmed (My University, 2021)
In almost all computer vision and perception based applications, particularly with camera and lidar; state-of-the-art algorithms are all based upon deep neural networks which require large amounts of data. Thus, the ability to label data accurately and quickly is of great importance. Approaches to semi-automated labeling (SAL) thus far have relied on using state-of-the-art object detectors to assist with labeling; however, these approaches still require a significant number of manual corrections. Surprisingly, none of these approaches have considered labeling from the perspective of multiple diverse algorithms. In this thesis a new framework for semi-automated labeling is presented, it is called F-SAL which stands for Fusion Based Semi-automated Labeling. Firstly, F-SAL extends on the idea of SAL through introducing multi-algorithm fusion with learning based feedback. Secondly, it incorporates new stages such as uncertainty evaluation and diversity evaluation. All the algorithms and design choices regarding localization fusion, label fusion, uncertainty and diversity evaluation are presented and discussed in significant detail. The biggest advantage of F-SAL is that through the fusion of algorithms, the number of true detections is either more or equivalent to the best single detector; while the false alarms are suppressed significantly. In the case of a single detector, to lower the false alarm rate, detector parameters must be adjusted, which trade lower false alarms for fewer detections. With F-SAL, a lower false alarm rate can be achieved without sacrificing any detections, as false alarms are suppressed during fusion, and true detections are maximized through diversity. Results on several datasets for image and lidar data show that F-SAL outperforms the single best detector in all scenarios.
Keywords: Machine Learning; Decision Fusion; Computer Vision; Labeling